'BUILDING IN THE DEEP': NOTES ON A METAPHOR FOR MENTAL ACITIVITY AND THE METAPHORICAL CONCEPT OF MIND IN EARLY GREEK EPIC*. (16th September 2016) - Horn, Fabian
Abstract : The verb βυσσο-δομεύω ( Sc . 30 = Hes. Frg. 195.37 M.–W.), separated by Glenn Most in his translation as 'planning in the depth', appears to be composed of a noun βυσσός ('depth') and a verbal root *δέμ- ('[to] construct'), thus literally meaning '(to) build in the deep'. There is no instance in our extant texts where this compound verb is employed literally in reference to an act of construction, and to the best of our knowledge it is exclusively used metaphorically in early epic diction to describe a mental process (see also Hom. Od . 4.676; 8.273; 9.316; 17.66, 465, 491; 20.184).